Corrigendum to: “Resistance to antibacterial therapy in pediatric febrile urinary tract infectionsda single-center analysis” [J Pediatr Urol 16 (2020) 71–79] (Journal of Pediatric Urology (2020) 16(1) (71–79), (S1477513119303389), (10.1016/j.jpurol.2019.10.018)) - Raupach, Thomas; Held, Jürgen; Prokosch, Hans-Ulrich; Rascher, Wolfgang; Zierk, Jakob (Journal of Pediatric Urology, 2022)
In order to fulfil the requirements of the doctoral office of the Friedrich-Alexander-University Erlangan-Nuremberg (FAU), the following updates have been made to the abovementioned article: Affiliation ‘a’ now reads as: Department of Pediatrics and Adolescent Medicine, Friedrich-Alexander-University Erlangen-Nuremberg (FAU), Erlangen, Germany. The following has been added to the Acknowledgements: The present work was performed in fulfilment of the requirements for obtaining the degree “Dr. med. (Doctor medicinae) at the Friedrich-Alexander University Erlangen-Nuremberg (FAU)”.
CRIS-Team Scopus Importer:2024-12-16